(untitled) - Edwards, Z. Colette (New York, 2005)
A practical guide to gastrointestinal and liver disorders for physicians and residents. This portable guide provides clinicians with high-yield information in a quick-review format. Includes the clinical entities most likely to be encountered in medical practice, on the boards, and recertifying exams.
Keywords: Gastroenterology,Gastroenterology,Nghiên cứu dạ dày-ruột,Nghiên cứu dạ dày-ruột